Aleida’s Poisonous Parenting Styles in Orange is the New Black - Chili Podang Bethari; Jenny Mochtar (Institute of Research and Community Outreach - Petra Christian University, 2023)
This paper aims to provide an analysis into the specific type of poisonous parenting style Aleida Diaz has in Orange is the New Black, the reason behind her adoption of such poisonous parenting styles and the resulting consequences on herself. In analyzing Aleida’s parenting, we use Dunham & Dermer’s theory of poisonous parenting styles, specifically the Dismissive and Contemptuous Parent, combined with Baumrind’s Uninvolved or Neglectful Parenting Style that includes consequences of such parenting styles. In addition, we also use Mother-Daughter Relationship theory to understand the underlying reason behind Aleida’s adoption of these poisonous parenting styles. We divide the analysis into three parts. In the first part, we analyze what kind of mother Aleida is. In the second part, we analyze why she adopts such parenting styles. In the third part, we analyze what consequences she experiences as a result of her poisonous parenting styles. Ultimately, the finding will reveal that there is a vicious cycle of these poisonous parenting styles that turns out to be difficult to break from one generation to the next.